NIGHT MARKET MANAGERS' RESPONSIBILITY TOWARDS CONSUMER SAFETY STANDARDS AT THE NAGA NUSANTARA NIGHT MARKET (MMTC) FROM THE MAQASID SYARIAH PERSPECTIVE - Ummu Aulia Nur Sitorus; Muhammad Ramadhan (Journal Analytica Islamica, 2025)
Night markets are one of the alternative forms of recreation for the public, offering various amusement rides at affordable prices. However, behind their appeal, night markets also carry significant safety risks for visitors, particularly related to the amusement rides. This study aims to examine the liability of the organizer regarding consumer safety standards for those harmed in accidents involving amusement rides at the Naga Nusantara Night Market, viewed from the perspective of Maqasid Shariah. The research method used is empirical legal research with a sociological approach, through the collection of primary data from direct interviews. The findings show that the lack of safety procedures and negligence in ride maintenance resulted in physical injury to consumers, which was resolved by providing compensation, representing a form of civil liability. From the perspective of Maqasid Shariah, however, such incidents violate the principle of hifẓ al-nafs (protection of life), which is one of the main objectives of Islamic law. Therefore, increased supervision, regular inspections, and safety education are necessary to ensure consumer rights and prevent similar incidents from recurring.